Electrical Component Measurement, Mechanics and Optics in Fundamental Physics-Laboratory Manual - Volume I - Yesigat , Anteneh (Electrical Component Measurement, Mechanics and Optics in Fundamental Physics-Laboratory Manual - Volume I, 2023)
This fundamental laboratory manual provides the experimental theory for the preparatory level, targeted on electrical component measurement, mechanics, and optical physics, into an experimental approach to be performed in the pre-college levels. This manual gives the necessary details to perform the experiments. The experiments included are meant to offer a basic understanding of Physics. Most of the experiments are designed to go hand in hand with the theoretical courses in Physics being taught during the first two semesters. For some additional experiments away from the theoretical background of the experiment, the laboratory procedure and data sheet are arranged for each experiment session in both Volume I and Volume II books. Some additional experiments away from the theory courses are being raised to enhance the scope of learning beyond the interdisciplinary physics courses that will integrate science with technology. The necessary theory for this type of experiment is described in the manual in a self-explanatory manner. However, all efforts are made to clarify any doubt by the teachers attractive in these laboratory classes.